2022
DOI: 10.1007/s13555-021-00676-9
|View full text |Cite
|
Sign up to set email alerts
|

Topical Ectoine Application in Children and Adults to Treat Inflammatory Diseases Associated with an Impaired Skin Barrier: A Systematic Review

Abstract: Introduction: Inflammatory skin diseases are a significant burden on affected patients. Inflammation is caused by various stress factors to the epidermis resulting in, e.g., dryness, redness, and pruritus. Emollients are used in basic therapy to restore the natural skin barrier and relieve symptoms. A systematic review was performed to evaluate the efficacy and safety of ectoine-containing topical formulations in inflammatory skin diseases characterized by an impaired skin barrier. Methods: A systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…It was initially described as a cell membrane protector with outstanding water-binding and stabilizing properties that could reduce transepidermal water loss, chemical and physical penetration, and subsequent inflammation. 20 At concentrations of 2% and higher, ectoine improves dryness and impaired skin barrier induced by UVA irradiation than with UV filters. Interestingly, the active association also preserved both in vitro Langerhans cells functionality and in vivo trans-UCA transformation to cis-UCA (known to be immunosuppressive 25 ), suggesting that it could protect skin from UV-induced immunosuppression.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was initially described as a cell membrane protector with outstanding water-binding and stabilizing properties that could reduce transepidermal water loss, chemical and physical penetration, and subsequent inflammation. 20 At concentrations of 2% and higher, ectoine improves dryness and impaired skin barrier induced by UVA irradiation than with UV filters. Interestingly, the active association also preserved both in vitro Langerhans cells functionality and in vivo trans-UCA transformation to cis-UCA (known to be immunosuppressive 25 ), suggesting that it could protect skin from UV-induced immunosuppression.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, ectoine, a cyclic amino acid produced by extremophile microorganisms, can prevent many UV/light consequences (Langerhans cells migration, 18 pro‐inflammatory cytokines release, 19 DNA damages, 17 sunburn cell formation 18 ). Moreover, ectoine was initially described as a cell membrane protector reducing transepidermal water loss, chemical and physical penetration, and subsequent inflammation, and effective in atopic skin and prevention of skin aging 20 . The present study aimed to characterize the photoprotection properties of an association of ectoine and mannitol and to investigate its additional photoprotection against UVA and UVB effect in humans in combination with UV filters based on the assessment of specific UV‐induced biomarkers (squalene, trans‐UCA, and catalase activity).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of halophilic microorganisms accumulate organic compatible solutes to maintain the balance of osmotic pressure of the intracellular and the external environment ( Gunde-Cimerman et al, 2018 ). Among them, ectoine was initially found in Ectothiorhodospira halochloris ( Galinski et al, 1985 ) and is widely used in the fields of food, cosmetics, and medicine ( Liu et al, 2021 ; Kauth and Trusova, 2022 ; Zhang H. et al, 2022 ). Recent studies have shown that there was also the native synthesis of ectoine in some microalgae ( Fenizia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The skin is the largest organ of the human body and is a complex human protective barrier, protecting the human body from external invasion and moisture loss through the physical and chemical barriers ( 8 ). Skin inflammation is attributed to the derangement of the epidermal barrier function ( 9 ).…”
Section: Introductionmentioning
confidence: 99%